2020
DOI: 10.1371/journal.pone.0237837
|View full text |Cite
|
Sign up to set email alerts
|

High burden of depression among cancer patients on chemotherapy in University of Gondar comprehensive hospital and Felege Hiwot referral hospital, Northwest Ethiopia

Abstract: Introduction Cancer, the most stressful event a person may experience often triggers depression. Depression among these groups of people, in turn, affects chemotherapy adherence, length of hospitalization, quality of life and cancer treatment outcome. Even though the problem is enormous studies that address it are limited. Therefore this study was conducted to determine the prevalence of depression and associated factors among cancer patients on chemotherapy in Felege-Hiwot referral hospital and University of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 30 publications
2
19
0
3
Order By: Relevance
“…The mean prevalence of depression based on previous study was around 13 % and using all assessment methods it varies from approximately 4 to 49 % [9]. However, another recent study showed the prevalence of depression among cancer patients on chemotherapy was 70.86 % [10]. This wide variation is due to several factors including the treatment setting, type of cancer included and method used to screen for symptoms (e. g. interview by trained psychiatrist or self-report instrument) [11].…”
Section: Resultsmentioning
confidence: 90%
“…The mean prevalence of depression based on previous study was around 13 % and using all assessment methods it varies from approximately 4 to 49 % [9]. However, another recent study showed the prevalence of depression among cancer patients on chemotherapy was 70.86 % [10]. This wide variation is due to several factors including the treatment setting, type of cancer included and method used to screen for symptoms (e. g. interview by trained psychiatrist or self-report instrument) [11].…”
Section: Resultsmentioning
confidence: 90%
“…On the other hand, it is lower than studies conducted in Ghana, 10 Egypt 12 and Gondar Ethiopia. 9 The discrepancy might arise from the tool difference.…”
Section: Discussionmentioning
confidence: 99%
“…Also, chemotherapy and length of treatment period had influenced to increase DS than their counterparts. This may be due to side effects of the treatment and the cost of the treatment (Baraki, Tessema & Demeke 2020). Literature reported that high incidence of depression among terminally ill cancer patients had been reported due to the higher levels of disabilities/impairments (Vachon 2006).…”
Section: Correlates Of Depressive Symptomsmentioning
confidence: 99%
“…Higher distress of cancer patients may lead to anxiety, depression or both (Smith 2015). Depression is a common comorbidity found in nearly 10% cancer patients, and it also causes harmful consequences on the quality of life (QoL) (Tian 2009), survival rates (Smith 2015; Baraki, Tessema, & Demeke 2020), treatment adherence (Pitman 2018), repeated hospitalization (Prieto 2002), and suicidal ideation (Yousaf 2005).…”
Section: Introductionmentioning
confidence: 99%